Introduction - Gursoy, Dogan (2018)
© 2018 selection and editorial matter, Dogan Gursoy and Christina G. Chi; individual chapters, the contributors. Destination marketing refers to all marketing efforts directed towards the increase of number of tourists and revenues in a destination (Nunkoo, Gursoy and Ramkissoon, 2013). Over the past several decades, destination marketing has witnessed a tremendous growth in the amount of information and knowledge generated by both academics and practitioners (Gursoy, Uysal, Sirakaya-Turk, Ekinci and Baloglu, 2014). The main reason for this tremendous growth is that as the number of destination offerings has been increasing rapidly over the years, researchers and practitioners have been trying to better understand visitors’ decision making processes and the factors that may influence those processes (Romero, 2017) because understanding the reasons and motivations of travellers for purchasing and consuming one of the many travel experiences offered by a number of destinations can enable destination marketing managers to develop effective marketing strategies to attract those customers to their destinations (Ladeira, Santini, Araujo and Sampaio, 2016). This understanding is even likely to become more critical as some destinations fiercely fight to protect their market share while others strive for larger tourism market share and income, especially those destinations which rely heavily on tourism earnings for their economies (Gursoy, Saayman and Sotiriadis, 2015).